THE ACTIVITY OF LOCAL GOVERNMENT IN FOSTERING THE DEVELOPMENT OF TOURIST BRAND PRODUCTS OF NATURAL VALUABLE AREAS OF THE LUBLIN VOIVODESHIP - Danuta Guzal-Dec (Polityki Europejskie, Finanse i Marketing)
The aim of this study was to identify the importance of branded tourism products as a factor in the development of communes located in natural valuable areas of the Lublin voivodeship, and to evaluate the activity of municipal authorities in preparing conditions for the creation of branded tourist products. Branding is expensive, so shaping brand products should involve many stakeholders, including the government. Environment in which communes operate makes it hard to imagine managing them without branding. Lack of recognition of various areas of the region is a factor slowing down the development of tourism, but it creates an opportunity of creating brands in line with the expectations of the authorities and residents. In the study diagnostic survey with a questionnaire interview was used. Research material comprised 30 questionnaires, interviews with the mayor. It has been shown that, within the surveyed communes, great natural and cultural values are little used by the local community as lucrative tourist branded products. Nonetheless, there were positive changes, taking up comprehensive coherent marketing activities.